Ex vivo specimen MRI and pathology confirm a rectosigmoid mesenteric waist at the junction of the mesorectum and mesocolon. (20th October 2019) - D'Souza, N.; Lord, A. C.; Shaw, A.; Patel, A.; Balyasnikova, S.; Tudyka, V.; Abulafi, M.; Moran, B.; Rasheed, S.; Tekkis, P.; Coffey, J. C.; Terlizzo, M.; et al.
Abstract: Aim: Continuity of the mesentery has recently been established and may provide an anatomical basis for optimal colorectal resectional surgery. Preliminary data from operative specimen measurements suggest there is a tapering in the mesentery of the distal sigmoid. A mesenteric waist in this area may be a risk factor for local recurrence of colorectal cancer. This study aimed to investigate the anatomical characteristics of the mesentery at the colorectal junction. Method: In this cross‐sectional study, 20 patients were recruited. After planned colorectal resection, the surgical specimens were scanned in a MRI system and subsequently dissected and photographed as per national pathology guidelines. Mesenteric surface area and linear measurements were compared between MRI and pathology to establish the presence and location of a mesenteric waist. Results: Specimen analysis confirmed that a narrowing in the mesenteric surface area was consistently apparent at the rectosigmoid junction. Above the anterior peritoneal reflection, the surface area and posterior distance of the mesentery of the upper rectum initially decreased before increasing as the mesentery of the sigmoid colon. These anatomical properties created the appearance of a mesenteric 'waist' at the rectosigmoid junction. Using the anterior reflection as a reference landmark, the rectosigmoid waist occurred at a mean height of 23.6 and 21.7 mm on MRI and pathology, respectively. Conclusion: A rectosigmoid waist occurs at the junction of the mesorectum and mesocolon, and is a mesenteric landmark for the rectum that is present on both radiology and pathology.